Method for improving performance of lithium iron phosphate by secondary calcination of iron phosphate

Through the treatment of iron phosphate, dispersant and perfluorosulfonic acid-based polymer, combined with secondary calcination technology, the problem of difficult to achieve both high sphericity and high compaction density in the preparation of lithium iron phosphate particles has been solved, significantly improving the electrochemistry of the material. performance and safety features.

CN119349532APending Publication Date: 2025-01-24DEYANG CHUANFA LONGMANG NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411468923.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the prior art, it is difficult to prepare lithium iron phosphate particles to take into account both high spherical shape and high compaction density, resulting in insufficient electrochemical performance and safety of the materials.

Method used

By mixed with iron phosphate and dispersing agent, paste, filtrate, dry and dry, and burn it once to get the first forefront -driven body, and then mix, filter, and dry it with the influenza sulfonic acid -based polymer solution to obtain the second foretoppers. Lithium sources, grinding, and secondary sintering are performed to obtain lithium iron phosphate.

Benefits of technology

It achieves high sphericity and high compaction density of lithium iron phosphate particles, improves the electrochemical properties of the material, including discharge specific capacity, rate performance and cycle stability, while improving the safety performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium battery positive electrode materials, and provides a method for improving the performance of lithium iron phosphate through secondary calcination of iron phosphate, and the method comprises the following steps: S1, mixing iron phosphate with a dispersant to obtain a mixture; s2, the mixture is sequentially subjected to pulping, filter pressing, drying and calcination, and a first precursor is obtained; s3, sequentially mixing, filtering and drying the first precursor and a perfluorosulfonic polymer solution to obtain a second precursor; and S4, sequentially mixing, grinding and sintering the second precursor and a lithium source to obtain the lithium iron phosphate. The compaction density of the lithium iron phosphate is larger than 2.6 g / cm < 3 >, the sphericity degree is larger than or equal to 0.8, the average particle size range is 300-500 nm, the first charge gram capacity is 160-165 mAh / g, the energy density is 110-115 mWh / g, and the rate performance 1C discharge ratio is larger than 93%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of battery positive electrode materials, and in particular relates to a method for improving the performance of lithium iron phosphate by secondary calcination of iron phosphate. Background Art

[0002] Lithium iron phosphate (LiFePO4, LFP for short) has an olivine structure and a stable three-dimensional lithium ion transmission channel, which enables lithium ions to be efficiently and reversibly embedded and removed during the charge and discharge process. In its molecular formula, lithium, iron, phosphorus, and oxygen elements exist in a specific ratio, giving lithium iron phosphate the characteristics of high safety and long life. At present, lithium iron phosphate has been widely used in the fields of power batteries and energy storage because of its advantages as a positive electrode material for lithium-ion batteries, such as high cycle stability, good safety performance, and high charge and discharge efficiency.

[0003] The current mainstream method for producing lithium iron phosphate is the iron phosphate method. The morphology, particle size, iron-phosphorus ratio, etc. of iron phosphate have a great influence on the electrochemical properties of lithium iron phosphate. However, adjusting the performance of the corresponding lithium iron phosphate by adjusting the morphology, particle size, iron-phosphorus ratio, etc. of iron phosphate has disadvantages such as long cycle, high cost and uncontrollable risks. Chinese patent CN1305147C discloses a method for preparing high-density spherical lithium iron phosphate as a positive electrode material for lithium-ion batteries, which generates spherical or quasi-spherical iron phosphate through reaction, and obtains spherical lithium iron phosphate after calcination, with an average particle size of 7-12μm and a tap density of 2.0-2.2g / cm3. Chinese patent CN116281931A discloses a method for preparing spherical lithium iron phosphate, which uses fully water-soluble raw materials for batching, and obtains a LiFePO4 / C composite material with a particle size range of 8-20μm through spray drying and calcination. Chinese patent CN101635347B discloses a method for preparing a high-density lithium iron phosphate positive electrode material, which adopts a three-stage intermittent roasting process, supplements a carbon source after each roasting, and then performs the next round of roasting after mixed grinding, so as to achieve the purpose of reducing the particle size of the primary particles of lithium iron phosphate and improving the carbon coating layer. Chinese patent CN116443840A discloses a lithium iron phosphate positive electrode material and a preparation method thereof, by preparing lithium iron phosphate semi-finished products with different particle sizes, and then mixing and firing the semi-finished products to prepare a lithium iron phosphate material with mixed large and small particles. Chinese patent CN115353084A discloses a one-step method for producing lithium iron phosphate using dihydrate iron phosphate as a raw material, preparing dihydrate iron phosphate, crushing it to form a nano-scale calcined raw material, and then sintering, crushing, screening, and demagnetizing to obtain a lithium iron phosphate material. The calcination process uses temperature-controlled calcination in different temperature sections, but the reaction mechanism of dihydrate iron phosphate is different from that of iron phosphate. The precursor is still undergoing glucose decomposition and trivalent iron is reduced to divalent iron in the 500-600°C section. Lithium iron phosphate nucleation and crystal growth occur in the 600-800°C high temperature section. The patent also does not mention the regulatory effect of the process on the particle size of the product. There are many patents in the prior art that disclose methods for improving the tap density and volumetric capacity of materials by spheroidizing lithium iron phosphate particles, but no evidence of particle spheroidization is given. The accumulation of slightly larger spheres will produce gaps, which require small particles to fill in order to increase the compaction density of the material. Therefore, it is difficult for the preparation method of lithium iron phosphate particles in the prior art to take into account both its high sphericity and compaction density. Summary of the invention

[0004] The present invention is used to solve the technical problem that it is difficult to simultaneously take into account the high sphericity and compaction density of lithium iron phosphate particles in the preparation method of the prior art.

[0005] Therefore, in view of the above-mentioned deficiencies in the prior art, the first object of the present invention is to provide a method for improving the performance of lithium iron phosphate by secondary calcination of iron phosphate, the method comprising the following steps:

[0006] S1, mixing ferric phosphate and a dispersant to obtain a mixture;

[0007] S2, beating, filtering, drying and calcining the mixture in sequence to obtain a first precursor;

[0008] S3, sequentially mixing the first precursor and the perfluorosulfonic acid polymer solution, filtering and drying to obtain a second precursor;

[0009] S4. Mixing, grinding and sintering the second precursor and the lithium source in sequence to obtain lithium iron phosphate.

[0010] Furthermore, the dispersant includes: one or more of acrylic acid, polyvinyl alcohol, polyethylene glycol, anionic surfactants, cationic surfactants and nonionic surfactants.

[0011] Furthermore, the mass ratio of the dispersant to the iron phosphate is (0.001-0.01):1.

[0012] Furthermore, the specific surface area of ​​the iron phosphate is 5 to 8 m 2 / g.

[0013] Furthermore, the solid content of the slurry formed by beating is 40-50%.

[0014] Furthermore, the calcination temperature is 300-400° C., and the calcination time is 0.5-1 h.

[0015] Furthermore, the mass proportion of the perfluorosulfonic acid polymer in the second precursor is 0.5-5%.

[0016] Furthermore, the molar ratio of the iron phosphate to the lithium source is 1:(1-1.05), and the lithium source includes one or more of Li2CO3 and LiOH.

[0017] Furthermore, the sintering temperature is 600-800° C., and the sintering time is 0.5-1 h.

[0018] The technical mechanism is:

[0019] (1) The addition of additives promotes the lattice reorganization of iron phosphate, making the particle morphology more rounded and the particle size smaller. This change in microstructure is conducive to the rapid diffusion of lithium ions in the material, reducing the migration path of lithium ions, thereby improving the rate performance and cycle stability of the material.

[0020] (2) The commercially available iron phosphate obtained after the first calcination is subjected to a second calcination at an appropriate temperature of 350-450°C, which can effectively remove the trace amount of crystalline water remaining in the anhydrous iron phosphate, further improve the purity and crystallinity of the material, and lay a solid foundation for subsequent chemical reactions and performance improvements.

[0021] (3) Perfluorosulfonic acid polymer is a high-performance ionic polymer with excellent corrosion resistance, high temperature stability and high electrochemical stability. The chemical structure of PFSA consists of a long-chain polymer backbone and sulfonic acid groups suspended from the backbone. Perfluorosulfonic acid polymers can serve as effective surface modifiers due to their unique chemical structure and physicochemical properties. When this polymer is mixed with the first precursor, they will adsorb on the surface of the iron phosphate particles to form a uniform coating. This coating can not only protect the iron phosphate particles from erosion by external environmental factors such as the electrolyte during subsequent preparation and battery use, but also improve the contact interface between the particles and improve the efficiency of the electrochemical reaction.

[0022] (4) Although perfluorosulfonic acid-based polymers do not directly provide high conductivity, they can indirectly improve the conductivity of the battery by increasing the wettability of the lithium iron phosphate particle surface and promoting the transmission of lithium ions.

[0023] (5) During the mixing and grinding process, the iron phosphate particles coated with the perfluorosulfonic acid polymer can reduce direct contact between particles due to the presence of the coating, thereby reducing the damage to the particle structure caused by the mechanical stress generated during the grinding process. At the same time, the coating also acts as a "binder" between particles, which helps to form a more compact and uniform accumulation of lithium iron phosphate particles during the sintering process, thereby improving the electrical contact between particles.

[0024] (6) The perfluorosulfonic acid-based polymer coating has excellent chemical stability and resistance to electrolyte corrosion. This coating can form a protective barrier on the surface of lithium iron phosphate particles to prevent harmful substances in the electrolyte from directly reacting with lithium iron phosphate, thereby slowing down the dissolution of active substances and structural damage. This is of great significance for improving the cycle stability of the battery and extending the battery life.

[0025] (7) During the sintering process, the perfluorosulfonic acid-based polymer coating acts as a sintering aid. It can promote the sintering bonding between lithium iron phosphate particles, reduce the sintering temperature or shorten the sintering time. At the same time, due to the presence of the coating, the direct contact and friction between the particles during the sintering process are reduced, reducing the energy consumption during the sintering process and the risk of particle breakage.

[0026] (8) Perfluorosulfonic acid-based polymers generally have good thermal stability and chemical inertness. During battery use, even if the battery experiences extreme conditions such as thermal runaway, this coating can slow down the spread of thermal runaway to a certain extent and reduce the risk of battery fire or explosion. This is of great significance for improving the safety performance of batteries.

[0027] (9) Combining secondary calcination with perfluorosulfonic acid polymer coating can fully utilize the advantages of both and achieve the following synergistic effects: Simultaneously improve high sphericity and compaction density: secondary calcination optimizes the particle morphology, making it closer to a sphere; perfluorosulfonic acid polymer coating further stabilizes this spherical morphology and promotes close packing between particles, thereby increasing the compaction density. Comprehensive improvement of electrochemical performance: By improving the degree of crystallinity, conductivity and structural stability of the material, the synergistic effect can significantly improve the discharge specific capacity, rate performance and cycle performance of the LiFePO4 material.

[0028] The second object of the present invention is to provide a lithium iron phosphate prepared by the method for improving the performance of lithium iron phosphate by secondary calcination of iron phosphate according to any one of the embodiments of the first object, wherein the lithium iron phosphate satisfies one of the following properties: compaction density>2.6g / cm 3 , sphericity ≥ 0.8, average particle size range is 300-500nm, first charge capacity is 160-165mAh / g, energy density is 110-115mWh / g, rate performance 1C discharge ratio > 93%.

[0029] The beneficial effects of the present invention are:

[0030] (1) When the modified iron phosphate is prepared into lithium iron phosphate positive electrode material, the reaction is more thorough and the diffusion rate of lithium ions is accelerated, which directly leads to a significant improvement in electrochemical performance, which is of great significance for improving the overall performance of the battery.

[0031] (2) The solution to the problem of high compaction density of lithium iron phosphate (more than 2.6g / cm 3 ) makes the material more widely and reliably used in electric vehicles, energy storage systems and other fields that pursue high energy density.

[0032] (3) The compacted density of the lithium iron phosphate obtained by the present invention is greater than 2.6 g / cm 3, sphericity ≥ 0.8, average particle size range 300 ~ 500nm, first charge capacity 160 ~ 165mAh / g, energy density 110 ~ 115mWh / g, rate performance 1C discharge ratio > 93%. Lithium iron phosphate materials have excellent performance in particle morphology, particle size distribution, compaction density and electrochemical properties, and are suitable for application scenarios with high requirements for energy density, rate performance and cycle stability, such as electric vehicles, energy storage systems and other fields. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0034] Example 1

[0035] This embodiment provides a method for improving the performance of lithium iron phosphate by secondary calcination of iron phosphate, comprising the following steps:

[0036] S11, the specific surface area is 5 to 8m 2 / g ferric phosphate and polyvinyl alcohol (CAS No.: 9002-89-5) are mixed to obtain a mixture; wherein the mass ratio of polyvinyl alcohol to ferric phosphate is 0.005:1;

[0037] S21, pulping, filtering, drying and calcining the mixture in sequence to obtain a first precursor; wherein the solid content of the pulping is 45%, the calcination temperature is 350° C., and the calcination time is 1 h;

[0038] S31, sequentially mixing the first precursor and a 10% mass concentration perfluorosulfonic acid polymer solution (Chemours D2020 DuPont), filtering and drying to obtain a second precursor; the mass proportion of the perfluorosulfonic acid polymer in the second precursor is 3%;

[0039] S41, sequentially mixing, grinding and sintering the second precursor and Li2CO3 to obtain lithium iron phosphate, wherein the molar ratio of iron phosphate to Li2CO3 is 1:1.02, the sintering temperature is 700°C, and the sintering time is 1 hour.

[0040] Example 2

[0041] The difference between this embodiment and embodiment 1 is that the mass ratio of polyvinyl alcohol to iron phosphate is 0.001:1.

[0042] Example 3

[0043] The difference between this embodiment and embodiment 1 is that the mass ratio of polyvinyl alcohol to iron phosphate is 0.01:1.

[0044] Example 4

[0045] The difference between this embodiment and embodiment 1 is that the calcination temperature is 300° C. and the calcination time is 0.5 h.

[0046] Example 5

[0047] The difference between this embodiment and embodiment 1 is that the calcination temperature is 400° C. and the calcination time is 0.5.

[0048] Example 6

[0049] The difference between this embodiment and embodiment 1 is that the mass proportion of the perfluorosulfonic acid polymer in the second precursor is 0.5%.

[0050] Example 7

[0051] The difference between this embodiment and embodiment 1 is that the mass proportion of the perfluorosulfonic acid polymer in the second precursor is 5%.

[0052] Example 8

[0053] The difference between this embodiment and embodiment 1 is that the molar ratio of iron phosphate to Li2CO3 is 1:1.

[0054] Example 9

[0055] The difference between this embodiment and embodiment 1 is that the molar ratio of iron phosphate to Li2CO3 is 1:1.05.

[0056] Example 10

[0057] The difference between this embodiment and embodiment 1 is that the dispersant is calcium lignin sulfonate (CAS: 8061-52-7).

[0058] Comparative Example 1

[0059] The difference between this comparative example and Example 1 is that no dispersant is added during the secondary calcination of the iron phosphate.

[0060] This comparative example provides a method for improving the performance of lithium iron phosphate by secondary calcination of iron phosphate, comprising the following steps:

[0061] S11, sequentially pulping, filtering, drying and calcining the iron phosphate to obtain a first precursor; wherein the solid content of the pulping is 45%, the calcination temperature is 350° C., and the calcination time is 1 h;

[0062] S21, sequentially mixing the first precursor and a 10% mass concentration perfluorosulfonic acid polymer solution (Chemours D2020 DuPont), filtering and drying to obtain a second precursor; the mass proportion of the perfluorosulfonic acid polymer in the second precursor is 3%;

[0063] S31, sequentially mixing, grinding and sintering the second precursor and Li2CO3 to obtain lithium iron phosphate, wherein the molar ratio of iron phosphate to Li2CO3 is 1:1.02, the sintering temperature is 700°C, and the sintering time is 1 hour.

[0064] Comparative Example 2

[0065] The difference between this comparative example and Example 1 is that the iron phosphate is not subjected to secondary calcination.

[0066] This embodiment provides a method for improving the performance of lithium iron phosphate by secondary calcination of iron phosphate, comprising the following steps:

[0067] S11, sequentially mixing iron phosphate and a 10% mass concentration perfluorosulfonic acid polymer solution (Chemours D2020 DuPont), filtering and drying to obtain a precursor; the mass proportion of the perfluorosulfonic acid polymer in the precursor is 3%;

[0068] S21, sequentially mixing, grinding and sintering the precursor and Li2CO3 to obtain lithium iron phosphate, wherein the molar ratio of iron phosphate to Li2CO3 is 1:1.02, the sintering temperature is 700° C., and the sintering time is 1 hour.

[0069] Comparative Example 3

[0070] The difference between this comparative example and Example 1 is that the iron phosphate is not fully coated with the sulfonic acid polymer.

[0071] This embodiment provides a method for improving the performance of lithium iron phosphate by secondary calcination of iron phosphate, comprising the following steps:

[0072] S11, the specific surface area is 5 to 8m 2 / g ferric phosphate and polyvinyl alcohol (CAS No.: 9002-89-5) are mixed to obtain a mixture; wherein the mass ratio of polyvinyl alcohol to ferric phosphate is 0.005:1;

[0073] S21, pulping, filter pressing, drying and calcining the mixture in sequence to obtain a precursor; wherein the solid content of the pulping is 45%, the calcination temperature is 350° C., and the calcination time is 1 h;

[0074] S31, sequentially mixing, grinding and sintering the precursor and Li2CO3 to obtain lithium iron phosphate, wherein the molar ratio of iron phosphate to Li2CO3 is 1:1.02, the sintering temperature is 700°C, and the sintering time is 1 hour.

[0075] Comparative Example 4

[0076] The difference between this comparative example and Example 1 is that the calcination temperature is 250° C. and the calcination time is 0.5 h.

[0077] Comparative Example 5

[0078] The difference between this comparative example and Example 1 is that the calcination temperature is 450° C. and the calcination time is 0.5 h.

[0079] The lithium iron phosphate obtained in the above Examples 1 to 10 and Comparative Examples 1 to 5 was tested for compaction density, sphericity, average particle size range, first charge gram capacity, energy density, and rate performance 1C discharge ratio. The results are shown in Table 1.

[0080] Table 1 Performance of lithium iron phosphate obtained in Examples 1 to 10 and Comparative Examples 1 to 5

[0081]

[0082] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for improving the performance of lithium iron phosphate by secondary calcination of iron phosphate, characterized in that: The method comprises the following steps: S1, mixing ferric phosphate and a dispersant to obtain a mixture; S2, beating, filtering, drying and calcining the mixture in sequence to obtain a first precursor; S3, sequentially mixing the first precursor and the perfluorosulfonic acid polymer solution, filtering and drying to obtain a second precursor; S4. Mixing, grinding and sintering the second precursor and the lithium source in sequence to obtain lithium iron phosphate.

2. The method for improving the performance of lithium iron phosphate by secondary calcination of iron phosphate according to claim 1, characterized in that: The dispersant includes one or more of acrylic acid, polyvinyl alcohol, polyethylene glycol and calcium lignin sulfonate.

3. The method for improving the performance of lithium iron phosphate by secondary calcination of iron phosphate according to claim 2, characterized in that: The mass ratio of the dispersant to the ferric phosphate is (0.001-0.01):

1.

4. The method for improving the performance of lithium iron phosphate by secondary calcination of iron phosphate according to claim 3, characterized in that: The specific surface area of ​​the iron phosphate is 5 to 8 m 2 / g.

5. The method for improving the performance of lithium iron phosphate by secondary calcination of iron phosphate according to claim 1, characterized in that: The solid content of the slurry formed by beating is 40-50%.

6. The method for improving the performance of lithium iron phosphate by secondary calcination of iron phosphate according to claim 1, characterized in that: The calcination temperature is 300-400° C., and the calcination time is 0.5-1 h.

7. The method for improving the performance of lithium iron phosphate by secondary calcination of iron phosphate according to claim 1, characterized in that: The mass proportion of the perfluorosulfonic acid polymer in the second precursor is 0.5-5%.

8. The method for improving the performance of lithium iron phosphate by secondary calcination of iron phosphate according to claim 1, characterized in that: The molar ratio of the iron phosphate to the lithium source is 1:(1-1.05), and the lithium source includes one or more of Li2CO3 and LiOH.

9. The method for improving the performance of lithium iron phosphate by secondary calcination of iron phosphate according to claim 1, characterized in that: The sintering temperature is 600-800° C., and the sintering time is 0.5-1 h.

10. Lithium iron phosphate prepared by the method for improving the performance of lithium iron phosphate by secondary calcination of iron phosphate according to any one of claims 1 to 9, characterized in that: The lithium iron phosphate meets one of the following properties: compaction density> 2.6g / cm 3 , sphericity ≥ 0.8, average particle size range is 300-500nm, first charge capacity is 160-165mAh / g, energy density is 110-115mWh / g, rate performance 1C discharge ratio > 93%.

Citation Information

Patent Citations

  • Preparation method of high-density lithium iron phosphate positive material

    CN101635347B

  • Method for producing lithium iron phosphate by taking iron phosphate dihydrate as raw material through one-step method

    CN115353084A

  • Preparation method of spherical lithium iron phosphate

    CN116281931A

  • Lithium iron phosphate positive electrode material and preparation method thereof

    CN116443840A

  • Method for preparing high-density spherical ferric lithium phosphate as anode material of lithium-ion battery

    CN1305147C

Cited By

  • Preparation method of high-compaction powder positive electrode material

    CN120922840A

  • Lithium iron phosphate positive electrode material and preparation method therefor, and lithium battery

    WO2026199909A1